Studying the intersystem crossing rate and triplet quantum yield of meso-substituted porphyrins by means of pulse train fluorescence technique - SENGE, MATHIAS (My University, 2016)
Excited state dynamics, particularly intersystem crossing, of a set of meso-substituted porphyrins bearing different electron-donor and acceptor groups was studied by pulse train fluorescence technique. Triplet quantum yield was found to be critically dependent on the nature of meso-substituents in the porphyrin system. Porphyrins with meso methoxyphenyl groups were found to show high triplet quantum yields (ϕT between 0.70 and 0.81). Moreover, the quantity of methoxyphenyl groups and the substitution pattern directly influence ϕT. Alternatively, porphyrins attached to nitrophenyl group possess low triplet quantum yield values (~0.3). The observed structure-properties relationships suggest new ways for tuning the optical properties of porphyrins via chemical modification.
PUBLISHED
Cited By :1 Export Date: 8 December 2016
Keywords: porphyrins; porphyrins